2012
DOI: 10.1007/s11606-012-2173-7
|View full text |Cite
|
Sign up to set email alerts
|

Access to Care After Massachusetts’ Health Care Reform: A Safety Net Hospital Patient Survey

Abstract: Patients with Commonwealth Care and Medicaid, the two forms of insurance most often newlyacquired under the reform, reported similar or higher utilization of and access to outpatient visits and rates of having a usual source of care, compared with the privately insured. Compared with the privately insured, a significantly higher proportion of patients with Medicaid or Commonwealth Care Type 1 (minimal cost sharing) reported delaying or not getting dental care (42.2 % vs. 27.1 %) or medication (30.0 % vs. 7.0 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…These measures have been widely used in other national and state-specific surveys. 32,33 Lack of a usual source of care was indicated by a "no" response to the question of whether respondents had a regular place to go for medical care (excluding emergency department visits). We assessed lack of confidence in getting needed care by the question of how confident respondents were that they could get the health care they need, with 4 response options ranging from very confident to not confident at all.…”
Section: Methodsmentioning
confidence: 99%
“…These measures have been widely used in other national and state-specific surveys. 32,33 Lack of a usual source of care was indicated by a "no" response to the question of whether respondents had a regular place to go for medical care (excluding emergency department visits). We assessed lack of confidence in getting needed care by the question of how confident respondents were that they could get the health care they need, with 4 response options ranging from very confident to not confident at all.…”
Section: Methodsmentioning
confidence: 99%
“…Despite growth in procedure rates among younger persons, the mean age of TJA recipients remains older than 60 years. Researchers have found that the newly insured in Massachusetts under Medicaid and state-subsidized private insurance after the introduction of health reform faced costrelated obstacles in obtaining care [16]. A similar concern was raised regarding cost pressures potentially resulting in reduced access to arthroplasties as physicians consider opting out of Medicare and Medicaid owing to reduced reimbursement by these health plans [9], although this has not occurred to any meaningful degree.…”
Section: Discussionmentioning
confidence: 99%
“…This also allowed us to examine the net effect of health care reform among a population that may move in and out of eligibility for free or subsidized care [31]. As such, the gains observed seem even more impressive in this context, despite persistent gaps in coverage between the disadvantaged and others [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Through these initiatives, the law sought to allow eligible poor adults to purchase affordable, low-cost insurance despite barriers to coverage [10,12]. Despite substantial uptake of these programs, a significant number of low-income MA adults remain uninsured as of mid-2011 [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation